The Road to Good Governance: Via the Path Less Accountable? The Effectiveness of Fiscal Accountability in Liberia - Krawczyk, Kelly; Sweet-Cushman, Jennie; Muhula, Raymond (Taylor and Francis, 2013)
Accountability mechanisms are touted as a path to “good governance.” But are accountability mechanisms a sure route to achieving the objectives of “good governance”? Limited case studies have offered inconsistent evidence (Blair, 2000; Charlick, 2001; Devas & Grant, 2003). But empirical evidence of the relationships among principles of good governance—high citizen participation, low levels of corruption, high-quality service delivery—and accountability mechanisms is lacking. We examine the effectiveness of accountability mechanisms in Liberia and find relationships between measures of county level fiscal accountability and measures of good governance do not always produce expected results, making fiscal accountability mechanisms no guarantee for achieving goals of good governance.